Frege e o antipsicologismo: uma abordagem históricoconceitual da disputa entre entidades abstratas e imagens mentais - Silva, Anderson Bogéa da (2009)
This research's main motivation is to understand how significant Gottlob Frege's criticism of psychologism was, in the nineteenth century, as well as to determine its real theoretical basis. One points to the most significant Fregean a ntipsychologist attacks, especially to Frege's arguments that support the antipsychologist criticism, having as one of the problems to attempt for psychologist reduction of logic. To this end, one understands as central to the ontological aspects. In this work, one will see Frege's point of view confroted with psychologism in naturalistic bases, as it emerges from nineteenth-century scientificism, leading clearly to an opposition between a knowledge based on empirical facts, on the one hand, and a speculative philosophical knowledge, on the other hand. In the end, one recognizes the Fregean undertaking against psychologism as preservation not only of the "objective non-effective", but also as recognition of the need for a priori speculation in philosophy itself.